Canadian Anaphylaxis Network-Predicting Recurrence after Emergency Presentation for Allergic REaction (CAN-PREPARE): a prospective, cohort study protocol. Issue 10 (31st October 2022) - Alqurashi, Waleed; Shaker, Marcus; Wells, George A; Collins, Gary Stephen; Greenhawt, Matthew; Curran, Janet A; Zemek, Roger; Schuh, Suzanne; Ellis, Anne; Gerdts, Jennifer; Kreviazuk, Cheryl; Dixon, Andrew; et al.
Abstract : Introduction: Anaphylaxis is a severe, potentially fatal multiorgan system manifestation of an allergic reaction. The highest incidence of anaphylaxis is in children and adolescents. Biphasic anaphylaxis (BA) is defined as the recurrence of allergic symptoms after resolution of an initial reaction. It has been reported to occur in 10%–20% of cases within 1–48 hours from the onset of the initial reaction. The dilemma for physicians is determining which patients with resolved anaphylaxis should be observed for BA and for how long. Guidelines for duration of postanaphylaxis monitoring vary, are based on limited evidence and can have unintended negative impacts on patient safety, quality of life and healthcare resources. The objectives of this study are to derive a prognostic model for BA and to develop a risk-scoring system that informs disposition decisions of children who present to emergency departments (ED) with anaphylaxis. Methods and analysis: This prospective multicentre cohort study will enrol 1682 patients from seven paediatric EDs that are members of the Paediatric Emergency Research Canada network. We will enrol patients younger than 18 years of age with an allergic reaction meeting anaphylaxis diagnostic criteria. Trained ED research assistants will screen, obtain consent and prospectively collect study data. Research assistants will follow patients during their ED visit and ascertain, in conjunction with the medical team, if the patient develops BA. A standardised follow-up survey conducted following study enrolment will determine if a biphasic reaction occurred after ED disposition. Model development will conform to the broad principles of the PROGRESS (Prognosis Research Strategy) framework and reporting will follow the Transparent Reporting of a multivariable prediction model for Individual Prognosis or Diagnosis Statement. Ethics and dissemination: Ethics approval has been received from all participating centres. Our dissemination plan focuses on informing clinicians, policy makers and parents of the results through publication in peer-reviewed journals and broadcasting on multiple media platforms. Trial registration number: NCT05135377 .